2018
DOI: 10.1080/09540121.2018.1476666
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous effect of short-term transfers for improving ART adherence among HIV-infected Tanzanian adults

Abstract: A recently concluded randomized study in Tanzania found that short-term conditional cash and food transfers significantly improved HIV-infected patients’ possession of antiretroviral therapy (ART) and reduced patient loss to follow-up (LTFU) (McCoy et al., 2017). We examined whether these transfers had differential effects within population subgroups. In the parent study, 805 individuals were randomized to one of three study arms: standard-of-care (SOC) HIV services, food assistance, or cash transfer. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, innovative interventions are needed for young people who are stable on ART, reducing the need for frequent clinic visits which impact on education, domestic responsibilities and social activities and can thus be a barrier to ART adherence. ] **Trial also reported in "Target population: all PLHIV prescribed ART" [57] For PLHIV initiated on ART but have disengaged from care, providing cash incentives shows distinct promise in improving retention in HIV care, for perinatal women living with HIV and those who are food insecure [83 •• , 84 •• ]. Amounts needed to make a difference are likely to be small, covering transport costs of getting to clinics and possibly making a minimal contribution to basic food items [81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, innovative interventions are needed for young people who are stable on ART, reducing the need for frequent clinic visits which impact on education, domestic responsibilities and social activities and can thus be a barrier to ART adherence. ] **Trial also reported in "Target population: all PLHIV prescribed ART" [57] For PLHIV initiated on ART but have disengaged from care, providing cash incentives shows distinct promise in improving retention in HIV care, for perinatal women living with HIV and those who are food insecure [83 •• , 84 •• ]. Amounts needed to make a difference are likely to be small, covering transport costs of getting to clinics and possibly making a minimal contribution to basic food items [81].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, food insecurity was not assessed which may limit the findings [ 56 ]. However, in Tanzania, conditional food and cash transfers did have a beneficial effect on ART adherence at 6 months (95% medication possession ratio) (adjusting for site, 58% (95% CI = 50, 66) SoC versus 76% (95% CI = 72, 80) intervention) particularly for food-insecure patients and those newly diagnosed [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we explored effect heterogeneity across the same subgroups as in an analysis of the original trial results (sex, age, wealth index and treatment delay between HIV diagnosis and ART initiation) with a Wald test of the interaction term at alpha=0.20, while expecting these analyses to be underpowered. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Of the 23 articles included, 15 (65%) articles reported randomised clinical trials [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], 4 (17%) non-randomised empirical studies [34][35][36][37] and 4 (17%) quantitative descriptive studies with cost-effectiveness analyses [38][39][40][41].…”
Section: Methodsmentioning
confidence: 99%